Thermal study of polymerase chain reaction with capillary tubes. (September 2021) - Abid, Hassan Ali; Ong, Jian Wern; Song, Zhixiong; Lin, Eric Shen; Liew, Oi Wah; Ng, Tuck Wah
Highlights: Thermal analysis of immersion PCR with capillary tubes more effectively done numerically than experimentally. The temperature field could be coupled with the fluid-structure interaction using a moving mesh physics module in COMSOL. In PCR using the tilt method, uniform temperature distributions could be obtained with 5s of settling time. In PCR using the classical method, translation speeds over 150 mm/min are needed to limit temperature drop to 10 °C. The tilt method offers a more effective way to implement extreme PCR with low volume reagents. Abstract: Polymerase Chain Reaction (PCR) amplifies specific deoxyribonucleic acid (DNA) targets whereby the reaction vessels are placed in high thermal inertia media and subjected to multiple cycles of discrete temperatures to effect denaturation, annealing and extension events. Precise temperature control and efficient heat transfer are crucial factors in achieving amplification reproducibility and reliability as well as in reducing the time required for PCR. Understanding the temperature distribution and transfer characteristics during PCR will facilitate system optimization to enhance the efficiency of DNA amplification. We describe a numerical thermal study investigating temperature profiles achieved using the classical method of manual transfer of PCR reaction vessels through a series of temperature-controlled media compared with that of a more recently reported method that displaces reaction vessels spatially by tilting through different temperature zones. It was found that while the classical method allows the reagent to achieve uniform temperature distribution, natural convection effects would necessitate translation speeds in excess of 150 mm/min in order to limit the reagent temperature drop to within 10 °C. With the tilt method, uniform temperature distributions as well as temperature settling times within 5 s could be attained. The simulation results demonstrated here indicate that the tilt method can be developed further to augment extreme PCR requiring less than 2s for each cycle. Graphical abstract: Image, graphical abstract